Determinan Agronomis Produktivitas Jagung - Sutoro Sutoro (Puslitbang Tanaman Pangan, 2015)
The national maize productivity is lower than its genetic potential of the variety. Maize yields varied among regions, due to differences of the technological practices, which mainly included seed quality and variety planted by farmers, rate of fertilizers and the availability of soil moisture. Productivity could be optimized by planting hybrid variety and supplying nutrients through fertilization and providing adequate soil moisture. Open pollinated variety was reported as more suitable for the suboptimum environment. To mitigate the climatic changes which were difficult to predict, proper cultivation techniques and water conservation were the determinant keys for increasing maize productivity. General climatic condition was not a limiting factor for producing maize in Indonesia. Expansion of planted area could be carried out on almost all kinds of farm-lands, provided the three determinant yield factors were implemented. When those program was implemented, it was suggested that Indonesia would reach self sufficiency in maize production.